The extent of activating the digital learning resources of learning difficulties teachers for the primary stage in Riyadh city - Sayed, Abdula‘al Abd El; Al-Mulehi, Arwa Abdulaziz Mohammed (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed to measure the extent of activating the digital learning resources in the primary learning difficulties in Riyadh city, and the type of study used descriptive analysis method for the nature of the study. The study sample was randomly selected among the learning difficulties teachers in the primary education office in north of Riyadh city, 20). The study tool was a questionnaire consisting of (29) paragraphs divided into three main axes, the questionnaire was tested for honesty and consistency, and was applied during the first semester of the year 1436-1437 AH. The results showed that the activation of the use of digital learning repositories in primary learning difficulties was average (2.392 out of 3), which is the average in the first category. The study participants agreed on the advantages of activating the digital learning repositories in the teachers of learning difficulties for the primary stage with an average of (2.491 of 3), which is average in the first category. They also agreed on the obstacles of activating the digital learning repositories in the primary learning difficulties of the teachers at an average of (2.36 out of 3), which is the average in the first category.The bottom line is that there is a difference in the opinions of the sample members towards the use of digital learning repositories, the advantages of activation of digital learning resources, and the obstacles to activation of digital learning repositories in the primary learning difficulties teachers.
Keywords: digital learning repositories; teachers of learning difficulties